Matthew L. Becker, Fundamental Theology. A Protestant Perspective. Second Edition. London: T&T Clark, Bloomsbury Publishing Pic. 2024. 735 pages - Lind, Martin (Journal of Anglican studies, 2025)
Matthew L. Becker, Fundamental Theology. A Protestant Perspective. Second Edition. London: T&T Clark, Bloomsbury Publishing Pic. 2024. 735 pages. - Volume 23 Issue 1